PATTERN OF JOINTS INVOLVEMENT IN KASHIN-BECK DISEASE: A LOCAL OSTEOCHONDROPATHY IN CHINA - Farooq, Umer; Xiong, Guo; Irshad, Romana; Yaqoob, Shehzad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Kashin-Beck Disease (KBD) is an endemic osteochondropathy. The disease starts in childhood and attacks the growth of joint cartilage, the joints become deformed and painful, and the worst forms result in dwarfism. The most frequent joints involved are the finger, wrist, ankles, knees and elbows. In this study the pattern of joints involved in KBD was studied. Methods: A total of 368 patients aged above 13 from 6 villages in endemic areas of the Shaanxi province, located in the northwest of China, were selected through multistage stratified sampling. The patients were diagnosed based on the clinical criteria for diagnosis of KBD. The patients were administered with a battery of questionnaires along with clinical examination for joint involvement. Results: The patients presented both as oligoarticular as well as polyarticular pattern. Smaller joints were more frequently involved with a proximal-distal pattern. The number of joints involved increased with the severity of the disease. Conclusion: Proximal smaller joints are more frequently involved in the disease. The involvement of bigger joints takes place in later stages of disease, i.e., in the second and third degree. The pattern of joint involvement shows some correlation with Rheumatoid Arthritis which needs further investigation and comparative studies. Keywords: Kashin-Beck Disease, Endemic, Osteochondropathy